Australia - Patmore, Greg (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 2002)
Abstract Australian labour history remains a vigorous area of intellectual activity. Labour History, the journal of the Australian society, is celebrating its 40th anniversary and publishes a considerable number of articles. Other important sources of Australian labour history such as books, national conference proceedings, and branch publications highlight the links between academic labour historians and the broader community. One important contribution of Labour/Le Travail to Australian labour historiography was the Australian/Canadian comparative labour history project, which gave Australians the confidence to organise national conferences and develop the comparative dimension of labour history.